Synthesis and properties of sulfur-functionalized triarylmethylium, acridinium and triangulenium dyes - Santella, Marco; Della Pia, Eduardo; Sørensen, Jakob Kryger; Laursen, Bo W. (Beilstein Journal of Organic Chemistry, 2019)
Triangulenium dyes functionalized with one, two or three ethylthiol functionalities were synthesized and their optical properties were studied. The sulfur functionalities were introduced by aromatic nucleophilic substitution of methoxy groups in triarylmethylium cations with ethanethiol followed by partial or full ring closure of the ortho positions with nitrogen or oxygen bridges leading to sulfur-functionalized acridinium, xanthenium or triangulenium dyes. For all the dye classes the sulfur functionalities are found to lead to intensely absorbing dyes in the visible range (470 to 515 nm), quite similar to known analogous dye systems with dialkylamino donor groups in place of the ethylthiol substituents. For the triangulenium derivatives significant fluorescence was observed (Φf = 0.1 to Φf = 0.3).
Keywords: acridinium dyes; aromatic nucleophilic substitution; fluorescent dyes; sulfur-functionalized dyes; triangulenium dyes; triarylmethylium

(untitled) - Lavis, L. D.; Raines, R. T. (ACS Chem. Biol., 2008)

(untitled) - Grimm, J. B.; Muthusamy, A. K.; Liang, Y.; Brown, T. A.; Lemon, W. C.; Patel, R.; Lu, R.; Macklin, J. J.; Keller, P. J.; Ji, N.; Lavis, L. D. (Nat. Methods, 2017)

(untitled) - Butkevich, A. N.; Lukinavičius, G.; D’Este, E.; Hell, S. W. (J. Am. Chem. Soc., 2017)

(untitled) - Kolmakov, K.; Hebisch, E.; Wolfram, T.; Nordwig, L. A.; Wurm, C. A.; Ta, H.; Westphal, V.; Belov, V. N.; Hell, S. W. (Chem. – Eur. J., 2015)

The Molecular Probes Handbook - Haugland, R. P. (Thermofischer Scientific, 2010)

(untitled) - Moerner, W. E.; Orrit, M. (Science, 1999)

(untitled) - Grimm, J. B.; English, B. P.; Chen, J.; Slaughter, J. P.; Zhang, Z.; Revyakin, A.; Patel, R.; Macklin, J. J.; Normanno, D.; Singer, R. H.; Lionnet, T.; Lavis, L. D. (Nat. Methods, 2015)

(untitled) - Lei, Z.; Li, X.; Luo, X.; He, H.; Zheng, J.; Qian, X.; Yang, Y. (Angew. Chem., Int. Ed., 2017)

(untitled) - Staudinger, C.; Borisov, S. M. (Methods Appl. Fluoresc., 2015)

(untitled) - Panchuk-Voloshina, N.; Haugland, R. P.; Bishop-Stewart, J.; Bhalgat, M. K.; Millard, P. J.; Mao, F.; Leung, W.-Y.; Haugland, R. P. (J. Histochem. Cytochem., 1999)

(untitled) - Song, X.; Johnson, A.; Foley, J. (J. Am. Chem. Soc., 2008)

(untitled) - Berezin, M. Y.; Achilefu, S. (Chem. Rev., 2010)

(untitled) - Meyer-Almes, F.-J. (Methods Appl. Fluoresc., 2017)

(untitled) - Bosson, J.; Gouin, J.; Lacour, J. (Chem. Soc. Rev., 2014)

(untitled) - Stępień, M.; Gońka, E.; Żyła, M.; Sprutta, N. (Chem. Rev., 2017)

(untitled) - Westerlund, F.; Hildebrandt, C. B.; Sørensen, T. J.; Laursen, B. W. (Chem. – Eur. J., 2010)

(untitled) - Laursen, B. W.; Sørensen, T. J. (J. Org. Chem., 2009)

(untitled) - Laursen, B. W.; Krebs, F. C.; Nielsen, M. F.; Bechgaard, K.; Christensen, J. B.; Harrit, N. (J. Am. Chem. Soc., 1998)

(untitled) - Laursen, B. W.; Krebs, F. C. (Chem. – Eur. J., 2001)

(untitled) - Laursen, B. W.; Krebs, F. C. (Angew. Chem., Int. Ed., 2000)

(untitled) - Hammershøj, P.; Sørensen, T. J.; Han, B.-H.; Laursen, B. W. (J. Org. Chem., 2012)

(untitled) - Laursen, B. W.; Reynisson, J.; Mikkelsen, K. V.; Bechgaard, K.; Harrit, N. (Photochem. Photobiol. Sci., 2005)

(untitled) - Bogh, S. A.; Simmermacher, M.; Westberg, M.; Bregnhøj, M.; Rosenberg, M.; De Vico, L.; Veiga, M.; Laursen, B. W.; Ogilby, P. R.; Sauer, S. P. A.; Sørensen, T. J. (ACS Omega, 2017)

(untitled) - Bogh, S. A.; Bora, I.; Rosenberg, M.; Thyrhaug, E.; Laursen, B. W.; Sørensen, T. J. (Methods Appl. Fluoresc., 2015)

(untitled) - Rich, R. M.; Stankowska, D. L.; Maliwal, B. P.; Sørensen, T. J.; Laursen, B. W.; Krishnamoorthy, R. R.; Gryczynski, Z.; Borejdo, J.; Gryczynski, I.; Fudala, R. (Anal. Bioanal. Chem., 2013)

(untitled) - Rich, R. M.; Mummert, M.; Gryczynski, Z.; Borejdo, J.; Sørensen, T. J.; Laursen, B. W.; Foldes-Papp, Z.; Gryczynski, I.; Fudala, R. (Anal. Bioanal. Chem., 2013)

(untitled) - Hall, M. D.; Yasgar, A.; Peryea, T.; Braisted, J. C.; Jadhav, A.; Simeonov, A.; Coussens, N. P. (Methods Appl. Fluoresc., 2016)

(untitled) - Sørensen, T. J.; Thyrhaug, E.; Szabelski, M.; Luchowski, R.; Gryczynski, I.; Gryczynski, Z.; Laursen, B. W. (Methods Appl. Fluoresc., 2013)

(untitled) - Wada, M.; Konishi, H.; Kirishima, K.; Takeuchi, H.; Natsume, S.; Erabi, T. (Bull. Chem. Soc. Jpn., 1997)

(untitled) - Laursen, B. W.; Nørgaard, K.; Reitzel, N.; Simonsen, J. B.; Nielsen, C. B.; Als-Nielsen, J.; Bjørnholm, T.; Sølling, T. I.; Nielsen, M. M.; Bunk, O.; Kjaer, K.; Tchebotareva, N.; et al. (Langmuir, 2004)

(untitled) - Sørensen, T. J.; Laursen, B. W. (J. Org. Chem., 2010)

(untitled) - Martin, J. C.; Smith, R. G. (J. Am. Chem. Soc., 1964)

(untitled) - Laleu, B.; Mobian, P.; Herse, C.; Laursen, B. W.; Hopfgartner, G.; Bernardinelli, G.; Lacour, J. (Angew. Chem., Int. Ed., 2005)

(untitled) - Herse, C.; Bas, D.; Krebs, F. C.; Bürgi, T.; Weber, J.; Wesolowski, T.; Laursen, B. W.; Lacour, J. (Angew. Chem., Int. Ed., 2003)

(untitled) - Bosson, J.; Labrador, G. M.; Pascal, S.; Miannay, F.-A.; Yushchenko, O.; Li, H.; Bouffier, L.; Sojic, N.; Tovar, R. C.; Muller, G.; Jacquemin, D.; Laurent, A. D.; et al. (Chem. – Eur. J., 2016)

(untitled) - Nicolas, C.; Bernardinelli, G.; Lacour, J. (J. Phys. Org. Chem., 2010)

(untitled) - Rosenberg, M.; Rostgaard, K. R.; Liao, Z.; Madsen, A. Ø.; Martinez, K. L.; Vosch, T.; Laursen, B. W. (Chem. Sci., 2018)

(untitled) - Rosenberg, M.; Santella, M.; Bogh, S. A.; Muñoz, A. V.; Andersen, H. O. B.; Hammerich, O.; Bora, I.; Lincke, K.; Laursen, B. W. (J. Org. Chem., 2019)

(untitled) - Simonsen, J. B.; Kjær, K.; Howes, P.; Nørgaard, K.; Bjørnholm, T.; Harrit, N.; Laursen, B. W. (Langmuir, 2009)

(untitled) - Hansch, C.; Leo, A.; Taft, R. W. (Chem. Rev., 1991)

(untitled) - Brown, H. C.; Okamoto, Y. (J. Am. Chem. Soc., 1958)

(untitled) - Laleu, B.; Herse, C.; Laursen, B. W.; Bernardinelli, G.; Lacour, J. (J. Org. Chem., 2003)

Dye Lasers - Drexhage, K. H. (Structure and Properties of Laser Dyes, 1973)

Colour and Constitution of Organic Molecules - Griffiths, J. (Academic Press, 1976)

(untitled) - Sørensen, T. J.; Kilså, K.; Laursen, B. W. (Chem. – Eur. J., 2015)

(untitled) - Sørensen, T. J.; Shi, D.; Laursen, B. W. (Chem. – Eur. J., 2016)

(untitled) - Westerlund, F.; Elm, J.; Lykkebo, J.; Carlsson, N.; Thyrhaug, E.; Åkerman, B.; Sørensen, T. J.; Mikkelsen, K. V.; Laursen, B. W. (Photochem. Photobiol. Sci., 2011)

(untitled) - Lueck, H. B.; McHale, J. L.; Edwards, W. D. (J. Am. Chem. Soc., 1992)

(untitled) - Lewis, L. M.; Indig, G. L. (Dyes Pigm., 2000)

(untitled) - Strickler, S. J.; Berg, R. A. (J. Chem. Phys., 1962)

(untitled) - Kotaskova, M.; Osman Oglou, O.; Helm, M. (Org. Biomol. Chem., 2014)